2005
DOI: 10.1074/jbc.m503002200
|View full text |Cite
|
Sign up to set email alerts
|

Roles for C16-ceramide and Sphingosine 1-Phosphate in Regulating Hepatocyte Apoptosis in Response to Tumor Necrosis Factor-α

Abstract: Tumor necrosis factor (TNF)-␣ signals cell death and simultaneously induces the generation of ceramide, which is metabolized to sphingosine and sphingosine 1-phosphate (S1P) by ceramidase (CDase) and sphingosine kinase. Because the dynamic balance between the intracellular levels of ceramide and S1P (the "ceramide/ S1P rheostat") may determine cell survival, we investigated these sphingolipid signaling pathways in TNF-␣-induced apoptosis of primary hepatocytes. Endogenous C 16 -ceramide was elevated during TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
152
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(166 citation statements)
references
References 48 publications
11
152
1
2
Order By: Relevance
“…Refs. [41][42][43]. Although Cer can be generated from SM in practically all cellular compartments via the activation of sphingomyelinases (SMases), it is the mitochondrial Cer that is associated with apoptosis, the Cer generated in other cellular compartments having no effect on this death mechanism (44).…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [41][42][43]. Although Cer can be generated from SM in practically all cellular compartments via the activation of sphingomyelinases (SMases), it is the mitochondrial Cer that is associated with apoptosis, the Cer generated in other cellular compartments having no effect on this death mechanism (44).…”
Section: Discussionmentioning
confidence: 99%
“…17,18,22 In line with this, it has been shown that ACDase overexpression prevented TNF-induced death in L929 cells, 21 whereas NCDase transfection protected rat hepatocytes from TNF-induced cell death through ASMase activation. 44 Ceramide Generation Through ASMase Contributes to Hepatocellular Death. The next question we addressed was whether ceramide signals hepatocellular death and whether hepatic I/R injury would be modulated by the generation of ceramide.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes were then isolated by a nonrecirculating in situ collagenase perfusion of the liver through cannulation of the inferior vena cava as previously described. 12,13 After isolation, hepatocytes were washed 3 times and centrifuged at 50g for 1 minute. Cell viability was consistently 90% as determined by trypan blue exclusion.…”
Section: Methodsmentioning
confidence: 99%